Couples treatment for interpersonal violence: A review of outcome research literature and current clinical practices - McCollum, Eric E.; Stith, Sandra M. (My University, 2010)
Conjoint couple treatment for Interpersonal Partner Violence (IPV) remains controversial despite a growing body of research and practice experience indicating that it can be effective and safe. In addition, developing typologies of couples who are violent suggest that a “one size fits all” treatment approach to IPV is not appropriate and conjoint treatment may have a place in the treatment of at least some couples. In this paper, we review the experimental studies and clinical practices of conjoint treatment. Based on this review, we suggest current best practices for this approach to treatment. Best practices include couples treatment as part of a larger community response to IPV, careful screening of couples for inclusion in couples treatment, modification of typical conjoint approaches to promote safety and on-going assessment of safety with contingency plans for increased risk.
Keywords: Intimate partner violence; Couples treatment; Domestic violence; Batterer treatment